2012
DOI: 10.1063/1.3677268
|View full text |Cite
|
Sign up to set email alerts
|

Collisionless distribution function for the relativistic force-free Harris sheet

Abstract: A self-consistent collisionless distribution function for the relativistic analogue of the force-free Harris sheet is presented. This distribution function is the relativistic generalization of the distribution function for the non-relativistic collisionless force-free Harris sheet recently found by Harrison and Neukirch [Phys. Rev. Lett. 102, 135003 (2009)] as it has the same dependence on the particle energy and canonical momenta.We present a detailed calculation which shows that the proposed distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…In contrast to the models described above, in this case the force balance is provided by the non-zero value of the shear magnetic field B y instead of the plasma pressure gradient. Subsequently, this model has been generalised for nonMaxwellian distribution functions of charged particles 48 , and relativistic plasmas 44 . Kinetic models of a force-free CS with a periodic transverse structure have also recently been developed 1 .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the models described above, in this case the force balance is provided by the non-zero value of the shear magnetic field B y instead of the plasma pressure gradient. Subsequently, this model has been generalised for nonMaxwellian distribution functions of charged particles 48 , and relativistic plasmas 44 . Kinetic models of a force-free CS with a periodic transverse structure have also recently been developed 1 .…”
Section: Introductionmentioning
confidence: 99%
“…The non-uniqueness of the 'inverse' approach was shown by Wilson and Neukirch [33] who showed that the P zz given in equation (33) can be obtained with distribution functions that have a different dependence on the Hamiltonian H s than in equation (34), but the same dependence on the canonical momenta. It was also shown in [40] how the forcefree Harris sheet distribution function (34) can be generalised to the relativistic regime.…”
Section: [3])mentioning
confidence: 99%
“…It is the v -dependence of A ⋆ [Eq. (8)] that produces the singularity. In order to regularize the singularity v in (8) can be replaced by an antisymmetric function g(z) with z = v /v 0 , where v 0 is some constant velocity [30,31,33].…”
Section: Drift Kinetic Theorymentioning
confidence: 99%
“…Since solving self consistently the kinetic equations is tough particularly in complicated geometries the majority of kinetic equilibrium solutions are restricted to one dimensional configurations in plane geometry, e.g. [1]- [8]. Of particular interest are equilibria with sheared toroidal and poloidal flows which play a role in the transition to improved confinement regimes in tokamaks and stellarators, though understanding the physics of this transition remains incomplete.…”
Section: Introductionmentioning
confidence: 99%